Critical evaluation of Direct Push technology for hydrostratigraphic aquifer characterization - Dietrich, Peter; Zschornack, Ludwig; Vienken, Thomas (Águas Subterrâneas, 2011)
Environmental site investigations require high resolution information about lithology and hydraulic properties of the subsurface for understanding and modeling of flow and fluid transport processes. This is especially true for complex structured sedimentary deposits where spatial variability of hydrogeological parameters governs flow processes in saturated aquifer systems. Traditional approaches usually cannot cope with the task of reliable high resolution aquifer characterization of such heterogeneous systems. Hence, adequate field methods for the derivation of subsurface parameters need to be developed and reliably applied to describe subsurface variability. In this regard, Direct Push technologies turn out to be a promising platform for tools and approaches capable for high resolution aquifer characterization. However, to further improve acceptance, these tools need further evaluation using numerical simulations, case studies and field tests.